2023
DOI: 10.1116/6.0002609
|View full text |Cite
|
Sign up to set email alerts
|

Rubidium focused ion beam induced platinum deposition

Abstract: This work presents characterization of focused ion beam induced deposition (FIBID) of platinum using both rubidium and gallium ions. Trimethylplatinum [(MeCp)Pt(Me)3] was used as the deposition precursor. Under similar beam energies, 8.5 keV for Rb+ and 8.0 keV for Ga+, and beam current, near 10 pA, the two ion species deposited Pt films at 0.90 and 0.73 μm3/nC, respectively. Energy-dispersive x-ray spectroscopy shows that Rb+ FIBID-Pt consists of similar Pt contents (49% for Rb+ FIBID and 37% for Ga+ FIBID) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that the composition and structure of materials created by FIBID respond to the identity of the ion beam. Thus, at an incident energy of 8.5 keV and an ion flux of 7.0 pA, Rb + -induced deposition generated Pt films with a composition of 25% C, 20% O, 49% Pt, and 5% Rb, whereas Ga + -induced deposition under similar conditions (8.0 keV, 8.5 pA) resulted in Pt films with a composition of 22% C, 14% O, 37% Pt, and 27% Ga. 27 This also underscores the fact that in Ga + FIBID, the grown deposits often contain significant Ga contamination, affecting properties such as conductivity. 34 In Ar + FIBID, ion implantation becomes negligible as gaseous Ar escapes during deposition.…”
Section: ■ Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous studies have shown that the composition and structure of materials created by FIBID respond to the identity of the ion beam. Thus, at an incident energy of 8.5 keV and an ion flux of 7.0 pA, Rb + -induced deposition generated Pt films with a composition of 25% C, 20% O, 49% Pt, and 5% Rb, whereas Ga + -induced deposition under similar conditions (8.0 keV, 8.5 pA) resulted in Pt films with a composition of 22% C, 14% O, 37% Pt, and 27% Ga. 27 This also underscores the fact that in Ga + FIBID, the grown deposits often contain significant Ga contamination, affecting properties such as conductivity. 34 In Ar + FIBID, ion implantation becomes negligible as gaseous Ar escapes during deposition.…”
Section: ■ Introductionmentioning
confidence: 89%
“…Trimethyl­(methylcyclopentadienyl)­platinum­(IV) (Me 3 PtCpMe, 99%) was purchased from Strem Chemicals and purified by several freeze–pump–thaw cycles until impurities such as H 2 O and air (N 2 and O 2 ) were no longer detected by MS. A cooled, inert, 15 × 15 mm 2 tantalum/tantalum oxide substrate (200 ± 5 K) was exposed to Me 3 PtCpMe vapor to produce nanometer-scale thick films of precursor molecules, as determined by the attenuation of the substrate (Ta 4f, IMFP = 1.7 nm) signal in X-ray photoelectron spectroscopy (XPS) as shown in Figure S1 in the Supporting Information. ,, At this temperature, Me 3 PtCpMe adsorbs to the substrate surface where the precursor film can be subjected to ion beam irradiation without the risk of thermal degradation or desorption. Based on other studies, we have assumed that the Pt films formed by IBID of Me 3 PtCpMe in this study are homogeneous. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation